Does the Credit-to-GDP Gap Predict Financial Crisis in Nigeria? - O, Ihejirika, Peters. (International Journal of Social and Administrative Sciences, 2020)
This study investigated the Credit-to-GDP Gap as an Early Warning Indicator (EWI) of banking/systemic crisis in Nigeria. Annual data on domestic credit to the private sector as a ratio of gross domestic product for the period 1981 to 2019 was used. The credit-to-GDP gap was calculated using the one-sided Hodrick-Prescott filter with Lamda set at 1600. The performance was analyzed using a couple of interrelated methods - the signal approach and the area under the receiver operating characteristic (AU-ROC) curve as well as graphical analysis for visualization. The results indicate that Credit-to-GDP Gap performs poorly in Nigeria with an area under the receiver operating characteristic (AU-ROC) curve of 63.68%. Further, this study shows that the Basel Committee on Banking Supervision’s (BCBS) recommendation that the prudential authorities set lower thresholds (L) at 2% above trend may not work for Nigeria as this study suggests an optimal threshold of 0.98%. This result emphasizes the need for prudential authorities to employ informed judgement in setting thresholds with a view to activating the countercyclical capital buffer on time before crisis occurs.